Evaluation Of Diagnostic Sensitivity of Wet Preparation Microscopy Using Koh for Detection of Fungal Agents from Keratitis Patients - Khokhar, Neeta D; Mulla, Summaiya A; Shah, Latika N; Vaghela, Geeta M (National Journal of Community Medicine, 2013)
Background: Keratitis is a common ophthalmic condition mostly caused by fungi. Apart from fungal culture, wet preparation using 10% Potassium hydroxide (KOH) for microscopic detection of fungal elements is a rapid and accurate method of laboratory diagnosis. Purpose: This prospective study was undertaken in order to evaluate the diagnostic sensitivity of wet preparation microscopy using KOH for detection of fungal agents from keratitis patients. Methodology: 103 samples of clinically suspected patients of keratitis attending tertiary care hospital between march 2010 and june 2011 were included. Samples like corneal swabs, corneal scrapings, corneal button, and corneo-scleral rim were collected aseptically after slit lamp examination, then transported to microbiology laboratory. Samples were processed for direct microscopy (gram stain and 10% KOH wet mount preparation) and culture. Culture positive isolates were identified based on morphology and standard biochemical tests. Data entry and analysis was done statistically. Results: From 103 samples, fungal culture was positive in 12%. Different fungus isolates include Aspergillus flavus (67%) and Candida spp (25%) were the leading fungi followed by Curvularis (8%). Direct microscopical examination using KOH wet preparation and gram’s stain had detected fungal elements in 83% and 75% samples respectively against culture results. Conclusion: Aspergillus flavus (67%), Candida spp (25%) and Curvularia spp (8%) was most common cause of fungal keratitis. Wet mount with KOH can be relied upon as the single most important screening tool for rapid diagnosis of fungal corneal ulcer and treatment should be dispensed on its basis.